Narrative temporality and Johannine symbolism - H. Ito (Acta Theologica)
How does narrative temporality affect the understanding of Johannine symbolism? To investigate this is the purpose of this article. The notion of narrative temporality is not new in the study of Biblical texts. However, there have not been many studies which make this notion their main thrust. Rather, generally speaking, it has merely been used as a “guide” or framework by which one can investigate some other important aspects such as the interpretation of a certain piece of literature, narrative, or part of a narrative. Against this background, this article wishes to put more focus on the possibility and impact this notion can provide in Biblical studies. In order to do this, this article takes up the subject of Johannine symbolism in the Fourth Gospel, especially the symbol of light, simply because it is not easy to understand. The more difficult the subject is, the clearer this notion can display its impact and usability in the readings of Biblical narratives.